Effects of Timing on Cell Biopsy from Pre-compacted Morula Stage Bovine Embryos on Subsequent Embryonic Development - Shirazi, Abolfazl; Borjian, Sara; Nazari, Hassan; Ahmadi, Ebrahim; Heidari, Banafsheh; Bahiraee, Amin (Journal of Reproduction & Infertility, 2010)
Introduction: Embryo biopsy has potential applications in molecular research processes in domestic animals, besides its application in sex determination in embryo transfer programs. The objective of the present study was to assess the in vitro development of bovine embryos biopsied on different days of precompacted morula stage. Materials and Methods: Slaughterhouse-derived oocytes were matured in vitro, fertilized (Day-0) by frozen-thawed, Percol-separated spermatozoa and cultured on oviductal cell monolayer. The embryos were subjected to cell biopsy on Days 2, 3, and 4 postinsemination at 4-16-cell stages. The data were analyzed using ANOVA and Chi-squared tests (SigmaStat, version 2). A p-value < 0.05 was considered significant.Results: Biopsies carried out at 16-cell stage (Day-4) resulted in 94% of embryos developing to the blastocyst stage, which was significantly higher (p < 0.05) than the ones biopsied at 8-cell stage on Day-4 (64%), and those undergoing the procedure on Day-3 (49% and 46% at 4-cell and 8-cell stages, respectively) and Day-2 (39% and 33% at 4-cell and 8-cell stages, respectively). No significant differences were observed between biopsied and non-biopsied embryos on a given day. The total cell number in biopsy-derived blastocysts ranged between 103 and 135. The difference in the number of total cells, dead cells and cell allocation to trophectoderm and inner cell mass between non-biopsied and biopsy-derived blastocysts was insignificant.Conclusion: Biopsy of bovine embryos at 4-16-cell stages had no adverse effects on in vitro developmental potentials and the 16-cell stage embryos, biopsied on Day-4 was the best stage for blastomere removal.
Keywords: Biopsy; Bovine; Embryo; Fertilization; In Vitro; Precompacted morula